Analisis Sentimen Opini Publik pada Channel Youtube Mata Najwa Menggunakan Metode SVM - Asmara Andhini; Fadilah Nuria Handayani; Intan Diasih; Nurmalitasari (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid development of social media, particularly the YouTube platform, has created an active and open space for public discourse. One prominent example is the program